Overview of the synthesis of MXenes and other ultrathin 2D transition metal carbides and nitrides - Verger, Louisiane; Xu, Chuan; Natu, Varun; Cheng, Hui-Ming; Ren, Wencai; Barsoum, Michel W. (Current opinion in solid state & materials science, 2019)
•MXenes constitute a family of 2D materials of about 30 different compositions.•Bottom-up synthesis enables the production high-quality thin 2D transition metal carbide and nitride films.•Different synthesis pathways have been reported that avoid the use of hazardous HF.•Solid solutions and chemical order in MAX phases have expanded the chemistry of MXenes. In 2011, a new family of two dimensional (2D) carbides, carbonitrides and nitrides – labeled MXenes – was discovered. Since then the number of papers on these materials has increased exponentially for several reasons amongst them: their hydrophilic nature, excellent electronic conductivities and ease of synthesizing large quantities in water. This unique combination of properties and ease of processing has positioned them as enabling materials for a large, and quite varied, host of applications from energy storage to electromagnetic shielding, transparent conductive electrodes, electrocatalysis, to name a few. Since the initial synthesis of Ti3C2 in hydrofluoric acid, many more compositions were discovered, and different synthesis pathways were explored. Most of the work done so far has been conducted on top-down synthesis where a layered parent compound is etched and then exfoliated. Three bottom-up synthesis methods, chemical vapor deposition, a template method and plasma enhanced pulsed laser deposition have been reported. The latter methods enable the synthesis of not only high-quality ultrathin 2D transition metal carbide and nitride films, but also those that could not be synthesized by selective etching. This article reviews and summarizes the most important breakthroughs in the synthesis of MXenes and high-quality ultrathin 2D transition metal carbide and nitride films.